Austen in Asia
XIV, 355 p. 18 illus., 9 illus. in color.
Keywords: This pioneering collection delves into Jane Austen's enduring legacy in the East, exploring her significance to East-West relations, Westernization, and Asian identities. It enriches Austen studies by integrating Asian viewpoints on feminism, queer theory, postcolonialism, and her reception and adaptations. The essays examine Austen's relevance in contemporary Asia, her historical ties to the region, and diverse Asian responses from the 20th century to recent adaptations. Spanning academic and popular media, it covers translations, critiques, and creative interpretations in various formats. Though not exhaustive, it offers insights from India, Pakistan, China, Taiwan, Korea, and Japan, contributing to a nuanced understanding of Austen's global impact. Tristanne Connolly is Professor of English at St. Jerome’s University in the University of Waterloo, Canada. She is the author of William Blake and the Body (2002) and several articles on British Romantic literature in relation to gender and sexuality, science and medicine, and religion. She has edited ten essay collections, and her digital edition of Erasmus Darwin’s The Loves of the Plants is forthcoming with Romantic Circles. Kimiyo Ogawa is Professor in the Department of English Studies at Sophia University, Tokyo, Japan. She is the author of The Ethics of Care and Empowerment (Tokyo: Kodansha, 2021), and the editor of Johnson in Japan (Bucknell University Press, 2020) with Mika Suzuki. She is interested in how advances in medical and physiological science informed representations of mind and human behaviour in a range of eighteenth-century novels. She co-hosted the Jane Austen & Co. online lecture series “Asia and the Regency” with Inger Brody and Anne Fertig. .